Ancient magic and ritual power - Meyer, Marvin W.; Mirecki, Paul Allan. (Religions in the Graeco-Roman World, 1995)
This volume contains a series of provocative essays that explore expressions of magic and ritual power in the ancient world. The essays are authored by leading scholars in the fields of Egyptology, ancient Near Eastern studies, the Hebrew Bible, Judaica, classical Greek and Roman studies, early Christianity and patristics, and Coptology. Throughout the book the essays examine the terms employed in descriptions of ancient magic. From this examination comes a clarification of magic as a polemical term of exclusion but also an understanding of the classical Egyptian and early Greek conceptions of magic as a more neutral category of inclusion. This book should prove to be foundational for future scholarly studies of ancient magic and ritual power. This publication has also been published in paperback, please click here for details.